(untitled) (Journal of Economic Research & Business Administration, 2024)
This paper presents a comparative analysis of the clients’ perception on the service robots’ usage in Kazakhstan, and Russia. The main idea is to find out the level of people’s understanding and acceptance of robotization in these neighbor countries, as these may influence the business development. The researchers adopted survey method to collect respondents’ views on the issue of interest. The research population includes people above 18 years of age in the two countries. The statistical results differ for the studied countries, with Russia where the respondents are more positive about the robotization, compared to Kazakhstan, where the respondents show lower interest in that development, 62% and 52% respectively (Figure 12). The main question of interest is would the implementation of robots affect negatively the number of visits to robotized businesses, e.g., bank offices, hotels and restaurants, etc. More than 43% of the respondents in Kazakhstan expressed dissatisfaction with the ethical aspect of robots usage (Russia – 18%), and 42% of Kazakhstanis reported that they fear job loss due to automation, in comparison with 23% of Russian respondents. This research contributes to the understanding of how the customers in the two studied countries consider the expected changes in the business and what may be their response to those changes. The limited number of respondents does not allow generalization of the results and conclusions, much bigger samples may be helpful to generalize. However, the findings are very informative and helpful in the decision-making process, as robotization requires financial investments and the attitude of the clientele about the quality of service they get is directly linked to the change of demand and business financial results. Based on these findings the hotel managers will be better prepared to decide if, when and how to introduce robots in the hotel business. Key words. Robotization, Artificial intelligence (AI), consumers’ attitude, services.